The Effect of Land Reform on Poverty: The Case of Southern African Development Community (SADC) Countries. Issue 1 (March 2014) - Nene, Gibson; Boubacar, Inoussa; Gitar, Bret
<x xml:space="preserve">Abstract</x> This article examines the effect of land reform on poverty in Southern African Development Community countries while controlling for factors that have been shown to be important in explaining poverty in Africa. The percentage of the population without access to clean water is used as a proxy for poverty. Empirical results provide evidence that countries that embarked on land reform experienced an increase in the percentage of the population without access to clean water for the period 1990–2007. More specifically, our results show that the impact of the willing seller–willing buyer land reform approach is higher than the impact of the expropriation land reform approach during the study period.